2012
DOI: 10.4414/smw.2012.13625
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral MRI and EEG studies in the initial management of pediatric headaches

Abstract: Despite abnormal findings on neurological/physical examination in a substantial number of children with headaches, the yield of pathological cMRIs was low. The use of EEG recordings was not contributory to the diagnostic and therapeutic approach. More research is needed to better define those patients who are likely to have an intracranial pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
6
0
4
Order By: Relevance
“…Twenty-one percent of imaged children (n ¼ 324) had abnormalities identified on MRI, largely incidental findings, with <1% having relevant findings to explain the headache, namely, tumor with hydrocephalus. Similarly, Martens et al [11] found that despite findings on neurologic and physical examinations in a substantial number of children with headaches, mostly migraines, the yield of brain MRI scans was low. Therefore, the yield of brain MRI is not contributory to the diagnostic and therapeutic approach.…”
Section: Discussion Of Procedures By Variant Variant 1: Child Primarmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one percent of imaged children (n ¼ 324) had abnormalities identified on MRI, largely incidental findings, with <1% having relevant findings to explain the headache, namely, tumor with hydrocephalus. Similarly, Martens et al [11] found that despite findings on neurologic and physical examinations in a substantial number of children with headaches, mostly migraines, the yield of brain MRI scans was low. Therefore, the yield of brain MRI is not contributory to the diagnostic and therapeutic approach.…”
Section: Discussion Of Procedures By Variant Variant 1: Child Primarmentioning
confidence: 99%
“…and the low yield of imaging in pediatric patients presenting with headaches alone bring into question the value of screening for patients with primary headaches. Pediatric headache literature has repeatedly reported that the value of neuroimaging in children with headache is generally low [9][10][11][12]. In a study by Yilmaz et al [12] of 449 children with headache, approximately 55% of children had migraine, 30% had tension-type headaches, 10% had secondary headaches, and 5% were unspecified.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Our findings are in concordance with those reports indicating an incidence of true TTH in children at levels between 5 and 15% of all pediatric headaches. [31][32][33][34] Some reports, however, give values as high as 48% or even 56% and large discrepancies can even be found in publications by the same author. For example, in two articles published by Seshia in 2004, the incidence of TTH was indicated as 18% in one publication and as 56% in the other.…”
Section: Discussionmentioning
confidence: 97%
“…There are a few studies on the characteristics of EEGs according to the type of headache and the implication of EEGs for headache patients. EEG abnormalities were reported to vary (8.8–20%) in pediatric headache patients ( 8 , 10 , 11 ), and the most common abnormalities were epileptiform discharge seen in 0.4–20% of the patients ( 12 18 ). Piccinelli et al reported electroencephalographic abnormalities in 12.8% of all children with headaches ( 8 ).…”
Section: Discussionmentioning
confidence: 99%